Enhancing the Predictive Value of SII and NLR in LAA Stroke: Addressing Unexplored Limitations and Future Directions [Letter] - Zhao E; Duan Z; Li J (Journal of Inflammation Research)
E Zhao,1 Zhengting Duan,2 Jingmei Li1 1Department of Rehabilitation, Guangyuan Central Hospital, Guangyuan, People’s Republic of China; 2Department of Rehabilitation, The First People’s Hospital of Guangyuan, Guangyuan, People’s Republic of ChinaCorrespondence: Jingmei Li, Department of Rehabilitation, Guangyuan Central Hospital, Guangyuan, People’s Republic of China, Email 13981261881@163.com